Impact of Metabolic Risk Factors on the Progression of Coronary Heart Disease: A Retrospective Cohort Study in Indonesia - Hanung Safrizal,; Muhammad Nur Aidi,; Sachnaz Desta Oktarina,; Alfons M Letelay, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Coronary Heart Disease (CHD) remains a significant global health issue, with its progression closely tied to metabolic risk factors, including dyslipidemia, hypertension, and diabetes. This study utilized secondary data from the Indonesia Ministry of Health's Cohort Study on Non-Communicable Disease (NCD) Risk Factors, spanning from 2011 to 2019, to examine the relationship between metabolic factors and CHD onset. Using the Cox Proportional Hazards (CPH) model, the study assessed the hazard ratios (HR) of key factors such as blood sugar, cholesterol, LDL, HDL, and blood pressure. The results showed that high blood sugar (HR = 1.93, p = 0.000), high cholesterol (HR = 2.68, p = 0.000), and high LDL (HR = 5.87, p = 0.000) were significant risk factors for CHD. Conversely, high HDL (HR = 1.66, p = 0.000) demonstrated a protective effect, while high blood pressure (HR = 6.85, p = 0.000) had the strongest association with disease progression. Kaplan-Meier survival curves further illustrated the decline in survival probabilities with increasing levels of these risk factors. These findings underscore the importance of managing metabolic risk factors to prevent and manage CHD.
Keywords: Cox proportional hazards; Coronary heart disease; Hypertension; Metabolic risk factors; Dyslipidemia